Assessing Herbivorous Impacts of Apohyale sp. on the Ulva prolifera Green Tide in China - Miao, Xiaoxiang; Xiao, Jie; Fan, Shiliang; Zang, Yu; Zhang, Xuelei; Wang, Zongling (Frontiers in Plant Science, 2021)
An epiphytic gammarid species, Apohyale sp., was abundant in the floating Ulva prolifera, which forms large-scale green tides in the Yellow Sea (YSGT). Field observation and laboratory experiments were subsequently conducted to study the species identity, abundance and grazing effects on the floating algal biomass. The abundance of Apohyale sp. showed great spatial variation, and varied from 0.03 to 1.47 inds g-1 in the YSGT. In average, each gram of Apohyale sp. body mass can consume 0.43 and 0.60 g algal mass of U. prolifera per day and the grazing rates varied among the algae cultured with different nutritional seawaters. It was estimated that grazing of Apohale sp. could efficiently reduce approximately 0.4% and 16.6% of the algal growth rates in Rudong and Qingdao, respectively. The U. prolifera fragments resulted from gnawing of Apohyale sp. had a higher growth rate and similar photosynthetic activities compared to the floating algae, indicating probably positive feedback on the floating algal biomass. This research corroborated the significant impact of Apohyale sp. on the floating algal mass of YSGT through the top-down control. However, further research is needed to understand the population dynamics of these primary predators and hence its correlation with expansion or decline of YSGT, especially under the complex food webs in the southern Yellow Sea.